A Phase 1, Single-center, Double-blind, Placebo-controlled Study in Healthy Subjects to Assess the Safety, Tolerability, Clinical Effects, and Pharmacokinetics–Pharmacodynamics of Intravenous Cyclopropyl-methoxycarbonylmetomidate (ABP-700) after a Single Ascending Bolus Dose - Struys, Michel M. R. F.; Valk, Beatrijs I.; Eleveld, Douglas J.; Absalom, Anthony R.; Meyer, Peter; Meier, Sascha; den Daas, Izaak; Chou, Thomas; van Amsterdam, Kai; Campagna, Jason A.; Sweeney, Steven P. (Anesthesiology (Philadelphia), 2017)
BACKGROUND:Cyclopropyl-methoxycarbonylmetomidate (ABP-700) is a new “soft” etomidate analog. The primary objectives of this first-in-human study were to describe the safety and efficacy of ABP-700 and to determine its maximum tolerated dose. Secondary objectives were to characterize the pharmacokinetics of ABP-700 and its primary metabolite (cyclopropyl-methoxycarbonyl acid), to assess the clinical effects of ABP-700, and to investigate the dose–response and pharmacokinetic/pharmacodynamic relationships. METHODS:Sixty subjects were divided into 10 cohorts and received an increasing, single bolus of either ABP-700 or placebo. Safety was assessed by clinical laboratory evaluations, infusion-site reactions, continuous monitoring of vital signs, physical examination, adverse event monitoring, and adrenocorticotropic hormone stimulation testing. Clinical effects were assessed with modified observer’s assessment of alertness/sedation and Bispectral Index monitoring. Pharmacokinetic parameters were calculated. RESULTS:Stopping criteria were met at 1.00 mg/kg dose. No serious adverse events were reported. Adverse events were dose-dependent and comprised involuntary muscle movement, tachycardia, and ventilatory effects. Adrenocorticotropic hormone stimulation evoked a physiologic cortisol response in all subjects, no different from placebo. Pharmacokinetics were dose-proportional. A three-compartment pharmacokinetic model described the data well. A rapid onset of anesthesia/sedation after bolus administration and also a rapid recovery were observed. A quantitative concentration–effect relationship was described for the modified observer’s assessment of alertness/sedation and Bispectral Index. CONCLUSIONS:This first-in-human study of ABP-700 shows that ABP-700 was safe and well tolerated after single-bolus injections up to 1.00 mg/kg. Bolus doses of 0.25 and 0.35 mg/kg were found to provide the most beneficial clinical effect versus side-effect profile.